2017
DOI: 10.3390/ijms18061147
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Regulation of NOD2 and RIG-I in Zebrafish Provides Insights into the Coordination between Innate Antibacterial and Antiviral Signaling Pathways

Abstract: Nucleotide-binding oligomerization domain-containing protein 2 (NOD2) and retinoic acid-inducible gene I (RIG-I) are two important cytosolic pattern recognition receptors (PRRs) in the recognition of pathogen-associated molecular patterns (PAMPs), initiating innate antibacterial and antiviral signaling pathways. However, the relationship between these PRRs, especially in teleost fish models, is rarely reported. In this article, we describe the mutual regulation of zebrafish NOD2 (DrNOD2) and RIG-I (DrRIG-I) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…RIPK2 is essential for the function of NOD2, with whom it forms a protein complex. While commonly associated with response to bacterial infection, NOD2 is increasingly recognized in response to both RNA and DNA viruses 5052 . By interacting with both the DDX58 and MAVS on the one hand 53 and with CARD18, PYCARD and CASP1 on the other 54 , the NOD2/RIPK2 complex is centrally positioned to serve as the integrator of both pathways.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK2 is essential for the function of NOD2, with whom it forms a protein complex. While commonly associated with response to bacterial infection, NOD2 is increasingly recognized in response to both RNA and DNA viruses 5052 . By interacting with both the DDX58 and MAVS on the one hand 53 and with CARD18, PYCARD and CASP1 on the other 54 , the NOD2/RIPK2 complex is centrally positioned to serve as the integrator of both pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RIG‐I negatively regulates NOD2‐induced NF‐κB signalling in mammals (Morosky, Zhu, Mukherjee, Sarkar, & Coyne, ). It has reported that knocking down RIG‐I expression by morpholino could enhance NOD2‐initiated NF‐κB activation, and vice versa (Nie, Xu, Xiang, Shao, & Chen, ). Therefore, the effects of RIG‐I on NOD2‐mediated NF‐κB activation were similar both in mammals and fish species.…”
Section: Antibacterial and Antiviral Functions Of Nlrs In Teleost Fishmentioning
confidence: 99%
“…Studies in mammals and zebrafish have shown that the LRR motif maintains NOD2 in an autoinhibition state, such that it cannot initiate signaling under physiological state without the stimulation of its ligand MDP (Girardin et al, 2003; Nie et al, 2017). After recognition of MDP by LRR, NOD2 undergoes self-oligomerization and recruits the downstream adaptor receptor-interacting serine/threonine-protein kinase 2 (RIPK2) through CARD-CARD interaction (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other teleost species, studies on NOD2 in zebrafish ( Danio rerio ) are the most comprehensive. For example, the structural model of the NACHT domain and ATP binding orientations, antibacterial and protective functions, induced NF-κB signaling pathways, and mutual regulation between NOD2 and RIG-I signaling in zebrafish have been well studied (Maharana et al, 2015; Nie et al, 2017; Oehlers et al, 2011; Zou et al, 2016). Other than zebrafish, preliminary studies on NOD2 in other teleosts, including grass carp ( Ctenopharyngodon idella ), Nile tilapia ( Oreochromis niloticus ), Indian major carp ( Catla catla ), rohu ( Labeo rohita ), orange-spotted grouper ( Epinephelus coioides ), miiuy croaker ( Miichthys miiuy ), and rainbow trout ( Oncorhynchus mykiss ) have been carried out (Basu et al, 2016; Chang et al, 2011; Chen et al, 2010; Gao et al, 2018; Hou et al, 2012; Li et al, 2015; Maharana et al, 2013).…”
Section: Introductionmentioning
confidence: 99%